Efectos del COVID-19 en la carga externa en el fútbol de alto nivel - Ramos Verde, E. J.; García Manso, J. M.; Díaz Díaz, R. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2022)
We analyzed the effect of the cessation of competition for COVID-19 on the physical performance of soccer players in the 1st Spanish division). The sample was stratified into three groups: 1st-3rd rounds; 25th-27th and 28th-30th. Pairwise comparisons were Student-t and Mann-Whitney U. We used a p-value of .0.05 as the criterion for statistical significance. Threshold values for evaluating effect size magnitudes were made using (Cohen's d). After the break, the distances traveled increased for the local and visiting teams. There was a slight decrease in high intensity efforts between post-confinement and the days (25th-27th). Compared the 1st and 3rd period, the values were slightly higher (rounds 28-30). The same was observed in those of accelerations and decelerations, with greater differences between the periods (1st and 3rd). There were differences when the resumption was compared with the days before the break.